A histopathological analysis of lung cancers. An 11-year retrospective study from Al-Madinah Al-Munawwarah, Saudi Arabia - Albasri, Abdulkader M. (Saudi Med J, 2019)
OBJECTIVES: To determine the histopathological pattern of lung cancers in Madinah, Saudi Arabia. METHODS: This retrospective histopathology-based study was conducted at the Department of Pathology, King Fahad Hospital, Madinah, Saudi Arabia and comprised cases of lung cancers for 11 years between January 2006 and December 2017. The data was obtained from histopathologic reports and evaluated for age, gender, site of tumor, and histopathological patterns with grade. RESULTS: A total of 138 patients with lung cancers were identified, 103 (74.6%) patients were males and 35 (25.4%) patients were females with a male to female ratio of 2.9:1. The ages ranged from 6 to 97 years with a mean age of 60.6 ± 14.7 years. Adenocarcinoma (AC) was the most common pathological type (47.8%), followed by squamous cell carcinoma (SCC) (25.3%), neuroendocrine tumor (8.7%) and metastatic carcinoma (8%). Both ACs and SCCs showed a male predominance with a ratio of 2.9:1 (male) and 4.8:1 (female). The majority of ACs (56.5%) and SCCs (65.7%) were moderately differentiated. CONCLUSION: The study established a baseline of lung cancer pattern on the basis of histopathological experience in a tertiary referral hospital in Al-Madinah Al-Munawwarah, Saudi Arabia. The results obtained showed similarities with that in the world literature and Saudi national studies.